The narrative in the Song of Songs - Fernandes, Gavin (2020)
Many believe the Song to be a loose collection of love poetry that lacks unity. That the Song evidences a loose unity has already been recognised (Pope & Elliott). This thesis provides evidence that any recognised unity is much stronger than has been touted and that the Song also contains a narrative. Narratology has demonstrated that certain types of lyric poetry can have narrative like events. In order to show evidence of a story, one has to demonstrate its “backbone” namely the existence of events that have a causative connection between them. If there is a love story especially, one would expect it to conform to a generalised set of scenarios. Not much has been written by way of narrative apart from the perspectives of dramatists who resort to importing fanciful meaning from outside the text. My work seeks to avoid these tendencies and employs techniques from narratology to examine the structure of the Song, the causality of events in the text, and its spatio-temporal dimension in order to establish a narrative in the Song. It also seeks to address other important issues like how lyric poetry might accommodate narrative; cohesion of what appears to be very disparate elements of the Song; and the meaning of some elusive metaphors and how these might contribute to a narrative. Comments from the examination include the following: “A very well written and highly convincing thesis that the Song can be understood as a lyrical narrative … ” “Demonstrated that an acknowledged, unsolved puzzle exists in scholarship about the structure of the Song, and posited an original solution … ” “There is some good originality in this thesis.” “Very convincing and well-argued. It should definitely be published in the scholarly arena.”